2017
DOI: 10.3390/s17020405
|View full text |Cite
|
Sign up to set email alerts
|

A Biocompatible Colorimetric Triphenylamine- Dicyanovinyl Conjugated Fluorescent Probe for Selective and Sensitive Detection of Cyanide Ion in Aqueous Media and Living Cells

Abstract: A colorimetric and turn-on fluorescent probe 1 bearing triphenylamine-thiophene and dicyanovinyl groups has been synthesized and used to detect cyanide anion via a nucleophilic addition reaction. Probe 1 exhibited prominent selectivity and sensitivity towards CN− in aqueous media, even in the presence of other anions such as S2−, HS−, SO32−, S2O32−, S2O82−, I−, Br−, Cl−, F−, NO2−, N3−, SO42−, SCN−, HCO3−, CO32− and AcO−. Moreover, a low detection limit (LOD, 51 nM) was observed. In addition, good cell membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Utilizing this sensing mechanism, Zi Hua et al synthesized and evaluated the sensing properties of a novel triphenylamine thiophene-based (with dicyanovinyl moieties) probe 47. The free probe exhibited pink non-fluorescent color due to the ICT mechanism [91], which further faded in the presence of CN − ions, accompanied by a fluorescence emission enhancement at 480 nm.…”
Section: Cyanidementioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing this sensing mechanism, Zi Hua et al synthesized and evaluated the sensing properties of a novel triphenylamine thiophene-based (with dicyanovinyl moieties) probe 47. The free probe exhibited pink non-fluorescent color due to the ICT mechanism [91], which further faded in the presence of CN − ions, accompanied by a fluorescence emission enhancement at 480 nm.…”
Section: Cyanidementioning
confidence: 99%
“…Utilizing this sensing mechanism, Zi Hua et al synthesized and evaluated the sensing properties of a novel triphenylamine thiophene-based (with dicyanovinyl moieties) probe 47 . The free probe exhibited pink non-fluorescent color due to the ICT mechanism [ 91 ], which further faded in the presence of CN − ions, accompanied by a fluorescence emission enhancement at 480 nm. Furthermore, the UV-Vis absorbance spectra revealed that only for CN − , spectral changes and color change of light pink to colorless under naked-eye and bright blue under UV light was observed.…”
Section: Thiophene Based Chemosensors For the Detection Of Anionsmentioning
confidence: 99%
“…Pertaining to artificial photosynthetic systems, even though the presence of TPA as sacrificial electron donor leads to the stabilization of the charge‐separated state due to hole migration, 27 the optical absorption localized majorly at around 300 nm hinders its use as a panchromatic dye. To address this, and transform TPA into a broad wavelength range absorber, the core of the molecule has been integrated with chromophores such as porphyrin, 27–37 corrole, 38,39 phenothiazine, 40 carbazole, 41 subphthalocyanine, 42 borondipyrromethene (BODIPY), 43–47 azaBODIPY, 48,49 metal complexes, 50,51 heterocyclics such as quinoxaline, 52 thiophene, 53 pyrrolopyrrole, 54 aryldiimides, 55–58 and various light‐harvesting molecules imposing potential applications in DSSCs, 20–23,26,56 OSCs, 17–19 and sensors 59–63 were prepared.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of fluorescence and colorimetric probes for the recognition of cyanide ion is established on coordination with metal ions or complex, displacement of copper ion ,, from copper complex, hydrogen-binding interaction, proton transfer, and reaction-based. However, for the detection of CN – in biological environment, it is very significant to develop a new strategy or method to detect CN – at very low concentrations in 100% aqueous medium. This challenge could be overcome by introducing the cyanide receptors on the surface of the vesicle.…”
Section: Introductionmentioning
confidence: 99%